Creación e implementación de videos instructivos para el uso correcto de los equipos biomédicos presentes en la Clínica Veterinaria, sede Circunvalar de la UAN (2023)
In Colombia, veterinary clinics lack specific regulations for the maintenance and use of biomedical equipment, unlike the mandatory regulations established for human health services. This deficiency can lead to damage to the equipment used in veterinary clinics, resulting in issues with patient safety, a lack of timeliness in service delivery, and high costs for the repair of biomedical equipment